Tinjauan Teori Hukum terhadap Tindak Pidana Pencurian yang Dilakukan Remaja Berumur 15 Tahun di Pasar - Damun Damun; Yasmirah Mandasari Saragih; Biner Sihotang (Pusat Riset dan Inovasi Nasional, 2026)
This research is motivated by the phenomenon of theft committed by 15-year-old adolescents in market environments, which creates tension between criminal law enforcement and the principle of child protection in the Indonesian legal system. The study aims to analyze the legal regulations of theft under the old Criminal Code (Law No. 1 of 1946), the new Criminal Code (Law No. 1 of 2023), and the Juvenile Criminal Justice System Law; to examine the criminal liability of adolescents from the perspective of criminal law theory; and to review the implementation of restorative justice and diversion. The research method used is normative legal research with statutory, conceptual, and case approaches, particularly reviewing the provisions of Article 591 of the new Criminal Code, the theory of fault, and the principle of proportionality. The results indicate that the criminal liability of children must take into account psychological limitations, maturity levels, and criminogenic factors, including the influence of the social environment. Furthermore, the mens rea element in the phrase